Feminist AI critical perspectives on data, algorithms and intelligent machines / edited by Professor Jude Browne, Dr Stephen Cave, Dr Eleanor Drage, Dr Kerry McInerney. - Browne, Jude, 1970-; Cave, Stephen, 1973-; Drage, Eleanor; McInerney, Kerry (Oxford scholarship online., 2023)
'Feminist AI' brings together leading feminist thinkers from across the disciplines to explore the impact of artificial intelligence (AI) and related data-driven technologies on human society.